Overcoming Difficulties Of Grade Iv Students Understanding The Tests Of Islamic Subjects With The Approach Of Islamic Religious Teacher Care At Sdn 04 Koto Ranah Lesson 2015/2016 - Masniwati Masniwati (Fakultas Sastra Universitas Ekasakti, 2018)
School is a place of formal education. All activities that occur within the school are directed and planned in such a way as to achieve a quality output. Quality output in education can be realized if supported by environmental components that work together and are responsible. Dirto Hadisusanto (2003: 157) states that education lasts a lifetime and is implemented within families, schools and communities, so that education is a shared responsibility between family, government and society. One indicator to know the level of quality of education conducted in schools is the achievement of student learning. Efforts to improve student achievement have been done by educational institutions either through the addition of learning facilities, curriculum improvement, teacher competency improvement, research, seminars and others. Based on the data analysis and hypothesis testing, the conclusion that can be taken in this research are: There is a negative and significant relationship between the anxiety test Islamic religion students with student achievement grade IV SDN 04 Koto Ranah District IV Nagari Bayang Utara Pesisir Selatan District Lesson 2015 / 2016 with a correlation coefficient of -0.220, so that the increasing anxiety of Islamic religious test students will be in line with the decrease in student learning achievement, and vice versa. There is a positive and significant relationship between the attention of teachers in the field of Islamic studies in the assessment of Islamic learning outcomes with the achievement of fourth grade students SDN 04 Koto Ranah District IV Nagari Bayang Utara Pesisir Selatan District Lesson Year 2015/2016 with a correlation coefficient of 0.268, so the increased attention Islamic teachers in the assessment of student learning outcomes will be in line with the increase in student achievement, and vice versa. Suggestion The Guru of Religion of Islam needs to give a sense of safety at the beginning of every test of Islam and as much as possible to get rid of the element of surprise from Islamic test situation by explaining the purpose and purpose of the test to the students, and give some examples about test of religion of Islam so that does not appear unexpected and not known by students who can cause anxiety to students. Parents need to increase attention in the assessment of students' learning outcomes for student achievement to increase, including attention to: repetition schedule, additional assignment (PR) from teachers, student learning activities, student retrieval scores, rapport filing, , notices of student learning difficulties by teachers, motivation, efforts to overcome learning difficulties and remedial and enrichment from teachers.